Peningkatan Kualitas untuk Mengurangi Kecacatan Kemasan Produk menggunakan Metode Six Sigma di PT. XY - Melky Maynaky; Iyan Bachtiar (Bandung Conference Series: Industrial Engineering Science, 2024)
Abstract. PT. XY is engaged in manufacturing the flexible packaging industry. Demand for packaging production has increased over time. This surge causes inappropriate/defective products to occur due to problems in the production process or errors made by machines and workers as well as an unsupportive environment. The aim is to find out, identify factors that cause defects in product packaging at PT. XY and provide improvements to factors causing defects in product packaging. The method used is Six Sigma with DMAIC stages which are integrated with several tools including the SIPOC diagram, CTQ Tree, Pareto diagram, DPMO, fishbone, FMEA, 5W+1H concept and Control Map. Based on the analysis of identifying problems that cause defects, there are several factors that cause Missprint defects, namely humans, machines, methods, materials and the environment. The control process efforts carried out by the company are in the form of a standardization process for the results of the improvements that have been proposed, so that the results of the improvements are always consistent so that they can achieve the 5.00-sigma target. resolve the problem of the type of Missprint defect first, if the type of Missprint defect has been repaired then the repair process continues to repair the next type of defect in accordance with the priorities that have been determined. Based on the results of the analysis that has been carried out, the objectives of this research can be achieved, including knowing the factors that cause defects and suggestions for improvements that the company can make. Abstrak. PT. XY bergerak pembuatan industri kemasan flexible packaging. Permintaan produksi kemasan melonjak naik seiring berjalannya waktu. Lonjakan ini menyebabkan produk yang kurang sesuai/cacat terjadi karena dalam proses produksi yang mengalami kendala atupun kesalahan yang dilakukan oleh mesin dan pekerja serta lingkungan yang kurang mendukung. Tujuannya mengetahui, mengidentifikasi faktor yang menyebabkan kecacatan pada kemasan produk di PT. XY dan memberikan perbaikan terhadap faktor penyebab kecacatan pada kemasan produk. Metode yang digunakan adalah Six Sigma dengan tahapan DMAIC yang diintegrasikan dengan beberapa alat diantaranya adalah diagram SIPOC, CTQ Tree, diagram pareto, DPMO, fishbone, FMEA, konsep 5W+1H dan Peta Kendali. Berdasarkan analisis identifikasi masalah penyebab cacat terdapat beberapa faktor yang menyebabkan jenis kecacatan Missprint yaitu manusia, mesin, metode, material, dan lingkungan. Upaya proses control yang dilakukan perusahaan berupa proses standarisasi hasil perbaikan yang telah diusulkan, agar hasil perbaikan selalu berjalan konsisten sehingga dapat mencapai target 5,00-sigma. penyelesaikan masalah dari jenis kecacatan Missprint terlebih dahulu, apabila jenis kecacatan Missprint selesai diperbaiki maka proses perbaikan dilanjutkan ke perbaikan jenis cacat selanjutnya sesuai dengan prioritas yang telah ditetapkan. Berdasarkan hasil analisis yang telah dilakukan maka tujuan dalam penelitian ini dapat dicapai diantaranya mengetahui faktor yang menyebabkan terjadinya cacat serta usulan perbaikan yang dapat perusahaan lakukan.